Catalogue of Notomastus M. Sars, 1851 (Annelida, Capitellidae) and the description of a new species from the Gulf of California - García-Garza, María Elena; de León-González, Jesús Angel; Tovar-Hernández, María Ana (Zootaxa, 2019)
Capitellids are burrowing, earthworm-like polychaetes. The taxonomy within the group presents significant difficulties, due in part to their relative simplicity. In this study, a catalogue of the capitellid genus Notomastus M. Sars, 1851, is presented and a new species is described from the Southern Gulf of California: Notomastus mazatlanensis sp. nov. The catalogue provides original names and synonymies for 43 species; type locality and location of type materials; records and remarks on systematics and distribution. Type material of 35 species were examined, 31 from which were photographed to illustrate the catalogue. Notomastus mazatlanensis sp. nov. is established based on the presence of finger-like branchiae emerging from the epithelium near to the notopodia. Branchiae are composed by 3–4 filaments, and the first chaetiger is uniramous. A taxonomic key for species distributed in the Gulf of California is presented. [Species name is register in ZooBank under urn: lsid: zoobank.org: pub:CC8A9E5A-7810-4272-A23C-DCB054E5B4EB]